Application of the ecosystem service concept for climate protection in Germany - Schetke, Sophie; Lee, Heera; Lautenbach, Sven (Ecosystem Services, 2018)
The implementation of the ecosystem services (ES) concept in planning and administration has gained momentum in Germany, so far the focus has been on landscape planning. We extend this research by exploring other legal domains such as urban planning and climate protection strategies and focus on climate protection and the use of renewable energies. This study analyzes all existing (n=13) climate protection laws and their drafts on federal state level in Germany, assessing their implicit and explicit use of the ES concept. 26 communal climate protection concepts on local level were also examined. Additionally, the sector of urban planning was considered through analysis of the climate protection amendment of the German Building Code (BauGB).
Available online 4 February 2017
Gesehen am 05.12.2018